Quality of life of patients with cancer - Kullmann, Lajos (Rehabilitacija (Ljubljana), 2008)
Quality of life evaluation of cancer patients is a challenging task due to the great variety of possibilities. The paper first gives an overview of the methods of quality of life assessment. Main target areas and conditions of the applicability are reviewed, including the use of proxy raters. For rehabilitation purposes the application of quality of life profiles are recommended. According to most researchers generic measures should complete the use of condition diagnosis or symptom specific instruments. The second part of the paper is based on a literature review. Review of the effects of therapeutic interventions at different cancer pathologies on the quality of life is mainly based on randomized controlled studies. Very few studies reported on significant improvement. Several systematic reviews evaluate methodological questions concerning quality of life assessment/measurement in cancer patients. The multitude of available measures may make any comparisons difficult. Well established, frequently used direct measures are preferred. Finally a few papers report on the effects of quality of life assessment on the communication between clients and professionals, and consequently on possible beneficial effect on quality of life of the assessed person.
Keywords: bolniki; kvaliteta življenja; onkologija; rak (medicina)